PENERAPAN TEKNIK RELAKSASI OTOT PROGRESIF PADA LANSIA PENDERITA HIPERTENSI DI RUANG FLAMBOYAN RST BHAKTI WIRA TAMTAMA SEMARANG - Kusumawati, Linda; Sonhaji, Sonhaji (NHM PRESS, 2024)
Background: Hypertension or what is better known as high blood pressure is a condition where blood pressure is above the normal threshold. The first complaint that many blood pressure sufferers experience is headache, usually in the neck (nape). One of the non-pharmacological treatments that can be done for hypertension sufferers is progressive muscle relaxation to relax the mind and body parts such as muscles and return the condition from a tense state to a relaxed, normal and controlled state effect of providing progressive muscle relaxation techniques on reducing blood pressure and pain in hypertension sufferers. Method: a case descriptive method, a nursing process approach including assessment, nursing diagnosis, nursing intervention, implementation and evaluation. The case study subjects were 2 elderly patients in hypertensive patients at Tamtama Hospital Semarang.. Results: after progressive muscle relaxation for 3 days decreased systolic, diastolic and pain scale blood pressure, the average decrease in the client's blood pressure for systolic and diastolic pressure was 10 mmHg. Conclusion: progressive muscle relaxation on reducing blood pressure in hypertensive patients